2021
DOI: 10.1177/26334941211024172
|View full text |Cite
|
Sign up to set email alerts
|

Double or dual stimulation in poor ovarian responders: where do we stand?

Abstract: Recent advances in our recognition of two to three follicular waves of development in a single menstrual cycle has challenged the dogmatic approach of ovarian stimulation for in vitro fertilization starting in the early follicular phase. First shown in veterinary medicine and thereafter in women, luteal phase stimulation–derived oocytes are at least as competent as those retrieved following follicular phase stimulation. Poor ovarian responders still remain a challenge for many decades simply because they do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
(177 reference statements)
0
12
0
Order By: Relevance
“…Protocols have even been developed for double stimulation (follicular and luteal phase ovarian stimulation) during the same menstrual cycle, known as DuoStim [19]. The goal is to maximize the number of gametes obtained, improving cumulative live birth rates without postponing cancer therapy [20][21][22].…”
Section: Embryo and Oocyte Cryopreservationmentioning
confidence: 99%
“…Protocols have even been developed for double stimulation (follicular and luteal phase ovarian stimulation) during the same menstrual cycle, known as DuoStim [19]. The goal is to maximize the number of gametes obtained, improving cumulative live birth rates without postponing cancer therapy [20][21][22].…”
Section: Embryo and Oocyte Cryopreservationmentioning
confidence: 99%
“…In fact, until recently, only retrospective, and non-randomized prospective studies have been performed to evaluate the increase of the number of oocytes in the second stimulation for women with POR. Most of the studies in the more recent review from Polat et al (2021) tend to show a slight increase in the number of oocytes in the luteal phase after a follicular stimulation ( Kuang et al , 2014a ; Vaiarelli et al , 2018 ). Only one small observational study reported more oocytes in the follicular than in the luteal phase with duostim (5.3 versus 3.8, respectively) ( Bourdon et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the understanding of multiple follicular waves within one menstrual cycle, double or triple ovarian stimulation and subsequent oocyte retrieval are being increasingly adopted by reproductive clinics ( Lu et al, 2021 ; Polat et al, 2021 ; Vaiarelli et al, 2020a ). Among them, dual/double stimulation (DS) is widely studied and performed, especially for women with poor ovarian responders (POR) and those in urgent need of fertility preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, dual/double stimulation (DS) is widely studied and performed, especially for women with poor ovarian responders (POR) and those in urgent need of fertility preservation. For POR with DS, patients got a better chance of getting more oocytes and subsequently more embryos for transfer ( Polat et al, 2021 ; Sighinolfi, Sunkara & La Marca, 2018 ). And the cumulative live birth rate (CLBR) also doubled when compared to FPS in these patients ( Vaiarelli et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%